PELUANG PEKERJA WANITA DALAM MEMILIH LAPANGAN PEKERJAAN PERTANIAN DAN NON PERTANIAN DI KOTA BATAM - Utomo, Agung Priyo (LPPM Universitas Terbuka, 2006)
Batam strategically located at the international shipping route; therefore it attracts investors and labor market. About 52% of citizens of Batam is female. The purpose of this research are to identify characteristics of female labor force; to recognize social and demographic factors that influence female labor in selecting job in the city of Batam; and to recognize the probability and tendency of female labor in selecting job by social and demographic aspects. The 2000 population census indicates that social and demographic characteristics influence the way female labor selecting jobs. There is a tendency that younger female labor is more interested working in non-agricultural sector. Female labors with high school education and higher education have larger probability to get jobs in non-agricultural sector as compare to female labor with lower education.